Ammonium acts systemically while nitrate exerts an additional local effect on Medicago truncatula nodules. (March 2020) - Schulze, Joachim; Liese, Rebecca; Ballesteros, Gabriel; Casieri, Leonardo; Salinas, Gabriela; Cabeza, Ricardo A.
Highlights: Nitrate and ammonium systemically induced a rhythmic pattern of symbiotic nitrogen fixation (SNF). The nitrate ion had a local effect on the nodule activity while ammonium did not. During the first hours after ammonium supply, the nodule transcriptome remained virtually unaffected. After nitrate supply downregulation was observed for genes encoding leghaemoglobin, NCR peptides and nicotianamine synthase. Abstract: Symbiotic nitrogen fixation (SNF) has a high energetic cost for legume plants; legumes thus reduce SNF when soil N is available. The present study aimed to increase our understanding regarding the impacts of the two principal forms of available N in soils (ammonium and nitrate) on SNF. We continuously measured the SNF of Medicago truncatula under controlled conditions. This permitted nodule sampling for comparative transcriptome profiling at points connected to the nodules' reaction following ammonium or nitrate applications. The N component of both ions systemically induced a rhythmic pattern of SNF, while the activity in control plants remained constant. This rhythmic activity reduced the per-day SNF. The nitrate ion had additional local effects; the more pronounced were a strong downregulation of leghaemoglobin, nodule cysteine-rich (NCR) peptides and nodule-enhanced nicotianamine synthase (neNAS). The neNAS has proven to be of importance for nodule functioning. Although other physiological impacts of nitrate on nodules were observed ( e.g. nitrosylation of leghaemoglobin), the main effect was a rapid ion-specific and organ-specific change in gene expression levels. Contrastingly, during the first hours after ammonium applications, the transcriptome remained virtually unaffected. Therefore, nitrate-induced genes could be key for increasing the nitrate tolerance of SNF.